2002
DOI: 10.1096/fj.01-0739fje
|View full text |Cite
|
Sign up to set email alerts
|

Role of vasodilator‐stimulated phosphoprotein in protein kinase A‐induced changes in endothelial junctional permeability

Abstract: At sites of ongoing inflammation, polymorphonuclear leukocytes (PMN, neutrophils) migrate across vascular endothelia, and such transmigration has the potential to disturb barrier properties and can result in intravascular fluid loss and edema. It was recently appreciated that endogenous pathways exist to dampen barrier disruption during such episodes and may provide an important anti-inflammatory link. For example, during transmigration, PMN-derived adenosine activates endothelial adenosine receptors and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
174
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(187 citation statements)
references
References 67 publications
(115 reference statements)
12
174
1
Order By: Relevance
“…Despite the extensive investigation of receptor splice variants, tissue specificity and differential activation, physiological significance of these differences remains to be explored Our results clearly demonstrate barrier-enhancing effects of PG in the pulmonary EC. Although involvement of PKA-dependent mechanisms in the PG protective effects on vascular endothelium has been recognized [19,51,52], the role of recently discovered Epac-Rap pathway in PG-mediated barrier regulation is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the extensive investigation of receptor splice variants, tissue specificity and differential activation, physiological significance of these differences remains to be explored Our results clearly demonstrate barrier-enhancing effects of PG in the pulmonary EC. Although involvement of PKA-dependent mechanisms in the PG protective effects on vascular endothelium has been recognized [19,51,52], the role of recently discovered Epac-Rap pathway in PG-mediated barrier regulation is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition PG-induced activation of PKA may cause actin cytoskeletal remodeling by Rac-independent mechanisms, for example, via phosphorylation of myosin light chain kinase and reduction of its enzymatic activity [38,65], or via phosphorylation of Rho regulatory protein RhoGDI leading to Rho inhibition [21,38], or via PKA-mediated phosphorylation of vasodilator-stimulated phosphoprotein (VASP) leading to the structural relaxation of the actin cytoskeleton linked to tight junctions via VASP -ZO-1 complex, which result in enhanced endothelial barrier function [52]. Importantly, our studies revealed strong protective effects of PG in the pulmonary EC model of thrombininduced barrier hyperpermeability and in the murine model of ventilator-induced lung injury ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Vasodilator-stimulated phosphoprotein (VASP) is a critical factor in regulating actin dynamics, and an increase in phospho-VASP is related to the increased levels of intracellular cAMP [4,10]. Treatment of B92 cells with IBMX and ISO increased phospho-VASP protein levels significantly in 10 min and slightly in 72 h compared with controls (Fig.…”
Section: Camp-stimulating Agents Promote Morphological Changesmentioning
confidence: 99%
“…VASP can associate with tight junctions via ZO-1 [Comerford et al, 2002], and bind with adherence junction via α-catenin [Reinhard et al, 2001]. These facts along with VASP ability to promote actin polymerization and assembly are thought to be a basis for VASPdependent regulation of cytoskeleton organization.…”
Section: Adhesion Complexes and Increased Transendothelial Permeabilitymentioning
confidence: 99%
“…VASP was long known as target for PKA and PKG phoshorylation; however, its involvement in PKA/PKG-mediated barrier protection remains a subject for further investigation. Although the level of phospho-VASP in endothelial junctional complexes seems to correlate with barrier enhancement in adenosinetreated endothelial cells [Comerford et al, 2002], other studies fail to show that elevated VASP phosphorylation is critical for PKA/PKG-dependent barrier enhancement [Schlegel et al, 2007;Rentsendorj et al, 2008].…”
Section: Adhesion Complexes and Increased Transendothelial Permeabilitymentioning
confidence: 99%